2012
DOI: 10.1097/pec.0b013e31826beb0c
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal Perforations in Neonatal Period

Abstract: Background Probiotic supplementation significantly reduces the risk of mortality and ≥ Stage II necrotising enterocolitis in preterm neonates. (Deshpande et al Lancet 2007, Pediatrics 2010. Based on the current evidence, experts favour routine probiotic supplementation in preterm neonates, if safe and effective products are available. We implemented a stepwise plan to introduce probiotics in our regional tertiary neonatal centre.Step wise approach:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 23 publications
0
15
0
Order By: Relevance
“…Bowel perforation is a life-threatening complication of NEC in premature infants [ 6 ]. This complication is associated with mortality as high as 76% [ 7 ] and long-term complications among survivors, such as short bowel syndrome, growth and developmental retardation, and adverse neurological outcome [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Bowel perforation is a life-threatening complication of NEC in premature infants [ 6 ]. This complication is associated with mortality as high as 76% [ 7 ] and long-term complications among survivors, such as short bowel syndrome, growth and developmental retardation, and adverse neurological outcome [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…GIPs can occur at any age, but are most common in the neonatal period as a complication of necrotizing enterocolitis [71112]. It may occur in older children as a result of trauma, other inflammatory gastrointestinal problems, or iatrogenic events, etc.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, the most common site of GIP is small intestine, in particular distal ileum[ 22 - 24 ]. Colon perforation is considered a rare event; however, in a recent study, Sakellaris et al[ 25 ] found colon perforation in 18.5% of newborns. According to literature reports, colon perforation is more common in high birth weight newborns (> 2500 g), which predominated in our study sample (65.7%)[ 26 ].…”
Section: Discussionmentioning
confidence: 99%